A fast charge‐Dependent atom‐pairwise dispersion correction for DFTB3. Issue 18 (26th February 2015) - Petraglia, Riccardo; Steinmann, Stephan N.; Corminboeuf, Clemence; Eisenstein, Odile; Fliegl, Heike; Hopmann, Kathrin H.; Mennucci, Benedetta
<x xml:space="preserve">Abstract</x> Organic electronic materials remarkably illustrate the importance of the "weak" dispersion interactions that are neglected in the most cost‐efficient electronic structure approaches. This work introduces a fast atom‐pairwise dispersion correction, dDMC that is compatible with the most recent variant of self‐consistent charge density functional tight binding (SCC‐DFTB). The emphasis is placed on improving the description of π‐π stacked motifs featuring sulfur‐containing molecules that are known to be especially challenging for DFTB. Our scheme relies upon the use of Mulliken charges using minimal basis set that are readily available from the DFTB computations at no additional cost. The performance and efficiency of the dDMC correction are validated on examples targeting energies, geometries, and molecular dynamic trajectories. © 2014 Wiley Periodicals, Inc.